Investigation for soliton solutions with some coupled equations - Zafar, Asim; İnç, Mustafa; Shakoor, Faiza; Ishaq, Muhammad (Springer, 2022)
The goal of this study is to investigate the soliton solution of the nonlinear coupled Higgs equation and the Maccari system with beta time derivative. Nonlinear partial differential equations are utilized to describe complex phenomenon in applied sciences. To acquire the soliton solutions of the given model equation with beta derivative, we apply the Sine-Gordon equation method. Numerical simulation with the graphical representation clearly reveals the high competence of the given algorithm. These solitons appear with constrictive requirements that ensure their existence, and they are also presented.
Keywords: The Maccari system; Sine-Gordon equation method; Coupled Higgs equation; Soliton solutions